Strong economic rights, weak political rights in the EU: a constitutional cacophony - Kouroutakis, Antonios (Edward Elgard, 2022)
From a legal and political perspective, the European Union (hereinafter EU) is a very ambitious project. On the one hand, it challenges the hierarchical structure of the ordinary constitutional systems of the Member States; on the other, it distorts the notion of national sovereignty and the unity of the political nature of the nation state. The core achievement of the EU, and its heart, is the Single Market, which allows the free movement of goods, services, capital and workers within the EU. The Single Market was founded in 1986 with the Single European Act, which was the first major revision of the Treaty of Rome and was projected to be established by 1992. In particular, the free movement of workers, which was first established with the Treaty of Rome, is currently a fundamental right guaranteed by the Treaty on the Functioning of the European Union (hereinafter TFEU).
Keywords: ODS 16 - Paz, justicia e instituciones sólidas